2001
DOI: 10.1051/0004-6361:20010980
|View full text |Cite
|
Sign up to set email alerts
|

A variable star survey of the open cluster M 37

Abstract: Abstract.A CCD photometric study of the dense galactic open cluster M 37 is presented and discussed. The majority of the analysed data are time-series measurements obtained through an RC filter. The observations were carried out on seven nights between December 1999 and February 2000, and have led to the discovery of 7 new variable stars in the field. Three of them have been unambiguously identified as W UMa-type eclipsing binaries, while two more are monoperiodic pulsating stars, most probably high-amplitude … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
59
0
1

Year Published

2002
2002
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 34 publications
(68 citation statements)
references
References 12 publications
8
59
0
1
Order By: Relevance
“…HW Vir itself was discovered by Menzies & Marang (1986), who determined the period. Kilkenny et al (1994) observed a change in the orbital period for the first time, which motivated further studies (e.g., Çakirli & Devlen 1999;Wood & Saffer 1999;Kiss et al 2000;Kilkenny et al 2000Kilkenny et al , 2003Ibanoǧlu et al 2004). Many possible explanations have been proposed and discussed, converging towards the existence of a third object with a long period and low mass.…”
Section: Appendix A: Notes On Individual Systemsmentioning
confidence: 75%
“…HW Vir itself was discovered by Menzies & Marang (1986), who determined the period. Kilkenny et al (1994) observed a change in the orbital period for the first time, which motivated further studies (e.g., Çakirli & Devlen 1999;Wood & Saffer 1999;Kiss et al 2000;Kilkenny et al 2000Kilkenny et al , 2003Ibanoǧlu et al 2004). Many possible explanations have been proposed and discussed, converging towards the existence of a third object with a long period and low mass.…”
Section: Appendix A: Notes On Individual Systemsmentioning
confidence: 75%
“…The masterlist was fed to DAOSPEC, Tsarevskii & Abakumov (1971), Dawson & Ianna (1998), and Bragaglia & Tosi (2006). (b) Averages of measurements by West (1967a), Jennens & Helfer (1975), Lyngå (1987), Mermilliod et al (1996), Twarog et al (1997), Kiss et al (2001), Kalirai et al (2001), Nilakshi & Sagar (2002), Grocholski & Sarajedini (2003), Bragaglia & Tosi (2006), and Hartman et al (2008). (c) Averages of measurements by McClure et al (1974), Barbaro & Pigatto (1984), Vandenberg (1985), Lyngå (1987), AnthonyTwarog et al (1990), Carraro & Chiosi (1994), Demarque et al (1994), Twarog et al (1997), Tadross et al (2002), and Grocholski & Sarajedini (2003).…”
Section: Linelist Atomic Data and Equivalent Widthsmentioning
confidence: 99%
“…(a) Star names and I C and R magnitudes from Dawson & Ianna (1998); coordinates and B and V magnitudes from Bragaglia & Tosi (2003); K S magnitudes from 2MASS. (b) Star names from van Zeipel & Lindgren (1921); coordinates from Kiss et al (2001); B and V magnitudes from Kalirai et al (2001); I C magnitudes from Nilakshi & Sagar (2002); K S magnitudes from 2MASS (c) Star names from Cannon & Lloyd (1970); coordinates from Stetson (2000) and Lasker et al (1990); B and V magnitudes from Anthony- Twarog et al (1990); I C and R magnitudes from Stetson (2000); K S magnitudes from 2MASS. (d) Star names from Fagerholm (1906); coordinates from Fan et al (1996); B, V and I C magnitudes from Sandquist (2004); B magnitude for star 286 and R magnitudes from Janes & Smith (1984); K S magnitudes from 2MASS.…”
Section: Introductionmentioning
confidence: 99%
“…The colour excess E(B −V ), apparent distance modulus (m − M ) and log (age) values determined by various investigators (see Table 1) for the cluster range from 0.27 to 0.31; 11.5 to 11.8 and 8.3 to 8.7 respectively. In the cluster region, Robin (1982) provides UBV electronographic magnitudes of mostly uncrowded stars up to a limiting magnitude in V ∼ 20 with an accuracy of 0.055 mag in V , Kiss et al (2001) 0.075 mag in B and 0.10 mag in U . The first variable star survey of M 37 carried out by Kiss et al (2001) using CCD observations discovered 7 new variables in the cluster region.…”
Section: Describe It As a Loosementioning
confidence: 99%
“…In the cluster region, Robin (1982) provides UBV electronographic magnitudes of mostly uncrowded stars up to a limiting magnitude in V ∼ 20 with an accuracy of 0.055 mag in V , Kiss et al (2001) 0.075 mag in B and 0.10 mag in U . The first variable star survey of M 37 carried out by Kiss et al (2001) using CCD observations discovered 7 new variables in the cluster region. Mermilliod et al (1996) presented radial velocity measurements for 55 red giants while Glushkova & Rastorguev (1991) published such measurements for 9 red giants.…”
Section: Describe It As a Loosementioning
confidence: 99%